Islam and Heritage in Europe Pasts, Presents and Future Possibilities - Puzon, Katarzyna; Macdonald, Sharon; Shatanawi, Mirjam (Critical Heritages of Europe, 2021)
Islam and Heritage in Europe provides a critical investigation of the role of Islam in Europe's heritage. Focusing on Islam, heritage and Europe, it seeks to productively trouble all of these terms and throw new light on the relationships between them in various urban, national and transnational contexts. Bringing together international scholars from a range of disciplines, this collection examines heritage-making and Islam in the context of current events in Europe, as well as analysing past developments and future possibilities. Presenting work based on ethnographic, historical and archival research, chapters are concerned with questions of diversity, mobility, decolonisation, translocality, restitution and belonging. By looking at diverse trajectories of people and things, this volume encompasses multiple perspectives on the relationship between Islam and heritage in Europe, including the ways in which it has played out and transformed against the backdrop of the 'refugee crisis' and other recent developments, such as debates on decolonising museums or the resurgence of nationalist sentiments. Islam and Heritage in Europe discusses specific articulations of belonging and non-belonging, and the ways in which they create new avenues for re-thinking Islam and heritage in Europe. This ensures that the book will be of interest to academics, researchers and postgraduate students engaged in the study of heritage, museums, Islam, Europe, anthropology, archaeology and art history. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-ShareAlike 4.0 International (see also http://creativecommons.org/licenses/by-sa/4.0/).